PENINGKATAN KOMPETENSI GURU DALAM PENGGUNAAN MEDIA PEMBELAJARAN/ALAT PERAGA MELALUI KEGIATAN IN HOUSE TRAINING (IHT) DI SD N 004 TEBING TINGGI KECAMATAN BENAI KABUPATEN KUANTAN SINGINGI - Syafrida (PGRI Provinsi Riau, 2021)
This study aims to find out to improve teacher competence in using learning media through In House Training (IHT) activities at SD Negeri 004 Tebing Tinggi, Kuantan Singingi District. The subjects in this study were all 8 teachers at SDN 004 Tebing Tinggi. Data collection techniques used are observation, interviews and documentation. The data were analyzed by using descriptive analysis techniques. The results showed that: (1) the implementation of In House Training, obtained the average value of all indicators in cycle I and cycle II with good criteria with an increase of 6.21 points. (2) Teacher performance improvement results in (a) pedagogic aspects, seen from the average score, the results obtained in cycle I with good criteria, while in cycle II with very good criteria, with an increase in value of 5.56. (b) Personality aspect, seen from the average value, the results obtained in the first cycle with good criteria, while in the second cycle with very good criteria, there was an increase of 5.56. (c) The social aspect of the average value in the first cycle with good criteria, while in the second cycle with very good criteria, with an increase of 8.51. (d) the professional aspect obtained the average score in the first cycle with good criteria, while in the second cycle with very good criteria, with an increase of 6.25. Therefore, it can be concluded that teacher competence in using learning media can be increased through IHT activities at SDN 004 Tebing Tinggi, Kuantan Singingi Regency.